Pengaruh Urutan Pencampuran Pemlastis pada Komponding Karet Terhadap Kinetika Vulkanisasi Menggunakan Model Deng-Isayev dan Kamal-Sorour - Saputra, Andri; Agustian, Mertza Fitra (Jurnal Teknik Kimia USU, 2024)
Plasticizers play an important role in the rubber industry to facilitate the dispersion of additives into rubber. This research aims to study the effect of plasticizer mixing sequence on vulcanization kinetics. This relates to its effect on printing time and energy, as well as the cost of electricity used. Compound A was made by adding plasticizer at the mastication stage and compound B was made by adding plasticizer at the masterbatch stage. Kinetic parameters were determined using Deng-Isayev and Kamal-Sorour models. The results show that the Deng-Isayev model is closer to the experimental data than the Kamal-Sorour model. Compound A has a k value (3.0635x10-6 sec-1) and cure index (0.8403) slightly lower than compound B with a k value 3.3511x10-6 sec-1 and cure index 0.9260. However, the mixing order of the plasticizers did not significantly affect the vulcanization performance, either the reaction speed constant, reaction order, induction time, optimal vulcanization time, and cure index.